Essays in Idleness - Kenko (London Wordsworth Classics, 1998)
A miscellany of aphorisms, musings and anecdotes; brief, witty and irreverent, this essay sketches the mundane world with urgency and humour, records the author's search for inner truth and urges the reader to the beauty in the transient and everyday.
Keywords: Japanese literature -- English literature -- Japanese essays